2004
DOI: 10.1262/jrd.50.445
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptional and Translational Regulations of Calbindm-D9k by Steroid Hormones and Their Receptors in the Uterus of Immature Mice

Abstract: Abstract. Calbindin-D9k (CaBP-9k) is a cytosolic calcium binding protein mainly expressed in the duodenum, placenta and uterus, and intestinal CaBP-9k is regulated by 1, 25-dyhydroxyvitamin D3. However, despite the presence of vitamin D receptors, uterine CaBP-9k is not under the control of vitamin D, but seems to be regulated by sex steroids. This steroids-dependent regulation of CaBP-9k is not only limited to a tissue-specific manner but also extends to a species-specific manner. In this study, we examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In duodenum, CaBP-9k and TRPV6 were shown to have a similar expression pattern; however, uterine CaBP-9k is regulated by different hormones and expressed at different stages of the estrous cycle (5,25). The expression of CaBP-9k is increased by E2 and at estrus in rats but its expression pattern is controlled by P4 and unaffected at diestrus in mice (1,12). In our previous study, uterine TRPV6 expression in rats was found to be similar to that of CaBP-9k expression in mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…In duodenum, CaBP-9k and TRPV6 were shown to have a similar expression pattern; however, uterine CaBP-9k is regulated by different hormones and expressed at different stages of the estrous cycle (5,25). The expression of CaBP-9k is increased by E2 and at estrus in rats but its expression pattern is controlled by P4 and unaffected at diestrus in mice (1,12). In our previous study, uterine TRPV6 expression in rats was found to be similar to that of CaBP-9k expression in mice (10).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for infertility in the knockout mice is abnormal ovarian function. The ovary is affected by changes in estrogen levels that induce cyclic ovulation [33]. Estrogen stimulates follicular responses to gonadtropins and activities of enzymes such as aromatase for steroidogenesis [34].…”
Section: Reproductive Organsmentioning
confidence: 99%
“…Instead, uterine CaBP9k and CaBP-28k are regulated by sex steroid hormones in rats [L'Horset et al, 1990[L'Horset et al, , 1993. In a previous report, P4 was shown to enhance CaBP-9k expression in the uteri of oophorectomized adult mice, whereas E2 had no effect [Tatsumi et al, 1999;An et al, 2004a]. In immature mice, it was shown that E2 induced the downregulation of uterine CaBP-28k expression [Opperman et al, 1992].…”
mentioning
confidence: 96%
“…In immature mice, it was shown that E2 induced the downregulation of uterine CaBP-28k expression [Opperman et al, 1992]. CaBP-9k is expressed at high levels in the mouse uterus in diestrus and metoestrus, and at basal levels in proestrus and estrus [Nie et al, 2000;An et al, 2004a]. CaBP-28k is expressed at high levels in human uteri in the mid-secretory phase.…”
mentioning
confidence: 99%